EFFECT OF COMBINED SPORTS ACTIVITIES ON CARDIOVASCULAR HEALTH STRUCTURES OF INACTIVE MEN FOLLOWING ADDICTION WITHDRAWAL - Mehdi Hasanali, Pakan Goudarzi, Soma Gholamveisy, (Chelonian Research Foundation, 2023)
Background and purpose: In fact, one of the concerns in drug treatment is related to the aspect of weight gain, body mass index (BMI), cholesterol increase and nutritional disorders after drug withdrawal. The purpose of this research is to investigate the effect of 8 weeks of combined sports activity on the structures of cardiovascular health in inactive men after quitting drugs. Materials and methods: The statistical population of this study was formed by inactive male drug addicts in Khorramabad city, who had been abstinent from drugs for at least two months, and 30 of them agreed to cooperate as a sample and were randomly selected in a ratio of 1: 1. They were divided into two experimental groups (15 people) and control (15 people). Sports activity of walking with 50-70% of the maximum heart rate and weight work with 45-50% of a maximum repetition was performed for eight weeks. 48 hours before and after eight weeks of sports activity, blood samples were taken to measure homocysteine, apoprotein A, HDL, and LDL. , fibrinogen of vulcocytes was performed. Analysis of covariance (ANCOVA) and Pearson's moment correlation coefficient were used for the inferential analysis of the data. Findings: 8 weeks of combined sports activity caused a significant decrease in the values of homocysteine, fibrinogen, and LDL leukocytes (P < 0.05). 8 weeks of combined sports activity caused a significant increase in the values of apoprotein A and HDL (P = 0.0001). The peak after eight weeks of combined sports activity increased significantly (P=0.0001). The inverse and significant relationship between fibrinogen (r=-0.76, P=0.001) and homocysteine (P=0.67, 0.001) (r=-), leukocyte count (r=-0.81, P=0.001) and BMI (r=-0.86, P=0.001), with peak VO2 after eight weeks. Discussion and conclusion: Eight weeks of combined sports activity reduces cardiovascular risk structures and improves cardiorespiratory fitness in inactive men after quitting drugs. Keywords: Sports Activities, Cardiovascular, Health Structures , Inactive Men ,Addiction